Impact of Psychiatric Comorbidities on Short-Term Outcomes Following Intervention for Lumbar Degenerative Disc Disease. Issue 19 (1st October 2018) - Kalakoti, Piyush; Sciubba, Daniel M.; Pugely, Andrew J.; McGirt, Matthew J.; Sharma, Kanika; Patra, Devi P.; Phan, Kevin; Madhavan, Karthik; Menger, Richard P.; Notarianni, Christina; Guthikonda, Bharat; Nanda, Anil; et al.
Abstract : Study Design: Retrospective, observational cohort study. Objective: To investigate the impact of psychiatric diseases on short-term outcomes in patients undergoing fusion surgery for lumbar degenerative disc disease (LDDD). Summary of Background Data: Limited literature exists on the prevalence and impact of psychiatric comorbidities on outcomes in patients undergoing surgery for LDDD. Methods: Adult patients (>18 yr) registered in the Nationwide Inpatient Sample database (2002–2011) and undergoing an elective spine fusion for LDDD that met inclusion criteria formed the study population. Defined primary outcome measures were discharge disposition, length of stay, hospitalization cost, and short-term postsurgical complications (neurological, respiratory, cardiac, gastrointestinal, wound complication and infections, venous thromboembolism, and acute renal failure). Multivariable regression techniques were used to explore the association of psychiatric comorbidities on short-term outcomes by adjusting for patient demographics, clinical, and hospital characteristics. Results: Of the 126, 044 adult patients undergoing fusion surgery for LDDD (mean age: 54.91 yr, 58% female) approximately 18% had a psychiatric disease. Multivariable regression analysis revealed patients with psychiatric disease undergoing fusion surgery have higher likelihood for unfavorable discharge (odds ratio [OR] 1.41; 95% confidence interval [CI] 1.35–1.47; P < 0.001), length of stay (OR 1.03; 95% CI 1.02–1.04; P < 0001), postsurgery neurologic complications (OR 1.25; 95% CI 1.13–1.37; P < 0.001), venous thromboembolic events (OR 1.38 95% CI 1.26–1.52; P < 0.001), and acute renal failure (OR 1.17; 95% CI 1.01–1.37; P = 0.040). Patients with psychiatric disease were also associated to have higher hospitalization cost (6.3% higher; 95% CI: 5.6%–7.1%; P < 0.001) compared to those without it. Conclusion: Our study quantifies the estimates for presence of concomitant psychiatric comorbid conditions on short outcomes in patients undergoing fusions for LDDD. The data provide supporting evidence for adequate preoperative planning and postsurgical care including consultation for mental health for favorable outcomes. Level of Evidence: 4 Abstract : Supplemental Digital Content is available in the text